Activities of measurement effectiveness management of supplies chains - Taraban, Kateryna (Management and Entrepreneurship: Trends of Development, 2017)
An urgent issue for the internal management of an industrial enterprise is the need to evaluate the effectiveness of supply chain management. The management of such chains and their individual elements must simultaneously ensure quality customer satisfaction while minimizing logistics costs. The subject of the study are theoretical-methodological and practical aspects of supply chain management. The purpose of the study is to analyze the performance indicators of supply chain management as a single system. The theoretical basis of the research is the methods of scientific knowledge and comparative method, structural-functional and systemic approaches are applied. The scientific significance of the work is to study the process of supply chain management in a changing environment. The use of modern principles of supply chain management is proposed to ensure the vital activity of domestic industrial enterprises.Research limitations/implications. The paper studies the process of supply chain management in a changing environment.Originality/value. Effective and rational logistic support of business plays an extremely important role in achieving high economic results. The logistics chain is an important category and object of management in the system of entrepreneurial logistics. The overall management of such a chain and its individual links has at the same time the provision of quality customer satisfaction and minimization Logistics costs. Consequently, to ensure the viability of domestic industrial enterprises, progressive management methods should be applied, namely the principles of logistic management to production.